BAGAIMANA MARKETING MIX DAN KEPUASAN KONSUMEN DALAM MENDORONG UGC INTENTION PADA KONSUMEN COFFEE SHOP DI KOTA SERANG? - Farah Putri Wenang Lusianingrum; Widya Nur Bhakti Pertiwi; Ina Riana; Kayla Maritza Nasution; Arum Wahyuni Purbohastuti (ITB AAS Indonesia Surakarta, 2026)
The purpose of this study is to understand the effect of the implementation of the 7P marketing mix on satisfaction and its impact on user content creation intention (UGC intention) among coffee shop consumers in Serang City, Banten Province. The urgency and relevance of this research are due to the increasing competition in the coffee shop industry and changes in digital consumer behavior that encourage consumers to act as content creators through social media. The quantitative research approach was chosen to assist in hypothesis testing using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The respondents used in the data analysis were 150 consumers selected using a purposive sampling technique. The respondent criteria were coffee shop consumers in Serang City who actively use social media and have visited a maximum of one visit in the past month. Data were collected through an online questionnaire. The hypothesis testing of this study confirmed that the implementation of the 7P marketing mix is ​​able to create customer satisfaction in coffee shops in Serang City. Furthermore, satisfied consumers tend to be more encouraged to share experiences, reviews, and recommendations related to products or services through various digital platforms. This empirical evidence reinforces the perspective of the Stimulus-Organism-Response (S-O-R) theory, where the implementation of the marketing mix as a stimulus can influence consumer satisfaction as an organism, which then results in a behavioral response in the form of UGC intentions. The implication is that coffee shop businesses need to create memorable and shareable consumption experiences to encourage consumer engagement in producing content on social media. Keywords: Marketing Mix 7P, Consumer Satisfaction, User Generate Content Intention